Determining Research Questions in e-learning - McAndrew, Patrick; Brasher, Andrew; Hardy, Pascale (Proceedings of the International Conference on Networked Learning, 2004)
In this paper we consider the future research direction for e-learning in relation to the needs of higher education. E-learning is recognised as a relevant method for the provision of learning across all areas of society and is considered of strategic importance at government level (HEFCE, 2003; DfES, 2003). In setting such strategies there should be sound knowledge of what approaches are effective and significant for the take up of e-learning. However, this would ignore the indications that there are weaknesses in the fundamental research that can inform such knowledge. Methods from other forms of research, such as comparative studies, often overlook the complexity of the learning process and the inevitable lack of impact from changes to methods of delivery. A critical review of the problems in supporting e-learning based on collation of expert views was carried out within a project, funded by the EU (eLearnTN, 2003). The results from that work led to proposed key research areas and research questions that need to be addressed as e-learning is introduced into existing or novel contexts. In particular a division can be made into research needs for work on measures of effectiveness, representation of effective learning designs, and methods to support knowledge sharing.